Promoting effects of campus football activities on the enhancement of adolescents' psychological qualities and the underlying mechanisms - Zheng, Wanting; Wang, Wenzi; Zhou, Chenglin; Zhang, Bin (Frontiers in Psychology, 2025)
BackgroundPsychological qualities issues among adolescents are increasingly prominent, and effective interventions are urgently needed. Campus Football Activities has shown potential in improving Psychological qualities, but the underlying mechanisms remain unclear.ObjectivesThis study aimed to explore the impact of campus football activities on adolescents' psychological qualities, along with the underlying mechanisms and pathways involved, and further examines the effects of an 8-week campus football program on adolescents' psychological qualities.MethodsFirst, an 8-week campus football intervention was conducted on 68 Chinese adolescents aged 16–18 years [mean age 16.865 years (standard deviation 0.636)] to explore the impact of campus football on adolescents' psychological qualities. Then, a cross-sectional survey was carried out on 431 adolescents from Chinese high school. The mean age of study participants varied from 16 to 18 years [mean 16.865 (0.816)]. The Sport Behavior Scale, Sport Cognitive Level Psychological Assessment Scale, Trait Sport Confidence Scale, and Adolescent Willpower Quality Scale were used to construct a structural equation model. This model revealed the effects of campus football on promoting adolescents' sports behavior, sports cognitive levels, confidence in sports, and willpower qualities, as well as their internal relationships.ResultsSignificant differences in campus football behaviors, sports cognitive levels, sports self-confidence, and willpower qualities existed among adolescents following campus football activities. Furthermore, the direct effect of campus football behaviors on willpower qualities was significant. The mediating and chain mediating effects of sports cognitive levels, sports self-confidence, and the combination of sports cognitive levels and sports self-confidence between campus football behaviors and willpower qualities were also significant.ConclusionCampus football activities can enhance adolescents' psychological qualities across: sports behaviors, sports cognitive levels, sports self-confidence, and willpower qualities. The internal action pathway is that campus football behaviors directly influence willpower qualities, and also improve willpower qualities through the respective mediating effects and joint chain mediating effect of sports cognitive levels and sports self-confidence.